Percutaneous transhepatic treatment of a unique portal vein malformation with portal hypertension in a pediatric patient - Paolo Marra; Ludovico Dulcetta; Claudia Pellegrinelli; Lorenzo D’Antiga; Sandro Sironi (CVIR Endovascular, 2021)
Abstract Background Anomalies of the portal venous system can be congenital or acquired, the latter being related to spontaneous thrombosis or iatrogenic alterations such as complications of perinatal catheterization of the umbilical vein. These conditions can be clinically silent for years and then manifest abruptly causing severe clinical emergencies. Case presentation This case report describes the diagnosis and interventional management of a singular abnormality in the portal venous system of an 8-year-old female that led to severe portal hypertension and acute variceal bleeding. Peculiar imaging findings were not pathognomonic for any of the known congenital and acquired portal vein anomalies: absence of a normal extrahepatic portal vein; splenic and mesenteric veins merging into a dilated left gastric vein; presence of an aberrant mesenteric venous collateral with a stenotic connection with the intrahepatic right portal branch; and absence of porto-systemic shunt. The case was successfully managed with percutaneous transhepatic portography and angioplasty. Conclusions Prompt non-invasive imaging characterization allowed to understand the singular vascular abnormality and mini-invasive interventional radiology management resolved portal hypertension and variceal bleeding.